The effect of remote treatment on medical provider creative thinking and patient disclosure: protocol for the MED-CREATE trial - Bouguettaya, Ayoub; Aboujaoude, Elias (Current controlled trials in cardiovascular medicine, 2025)
Background Open doctor-patient communication is essential for accurate diagnosis and effective treatment. However, the communication modality (video consultation vs. in-person visit) may impact the process and create tradeoffs. Previous research suggests that while online communication negatively affects creative thinking, it can also enhance disclosure. This study seeks to investigate how the communication modality utilized in medical settings influences both creative idea generation on the part of clinicians and disclosure on the part of patients. Drawing upon established frameworks in health literacy, social identity theory, and cognitive psychology, we aim to examine how different communication modalities impact doctors’ ability to generate solutions to clinical problems and patients’ willingness to open up about these problems. Methods/design This open-label, randomized controlled trial will recruit a sample of medical students in their final year and actors simulating patients. Participants will be randomly assigned to either online video consultations or in-person visits. During these consultations, medical students will be presented with patient cases involving participants told to act out conditions (i.e., real people given a script and told to pretend it represents their story and their symptoms) and tasked with interviewing the patients and generating potential diagnoses. The primary outcomes of the study will be threefold: (1) the number of ideas generated by medical students regarding the diagnosis (“differential diagnosis”—regardless of being correct or incorrect), (2) whether or not the accurate diagnosis is reached, and (3) patients’ tendency toward disclosure. Discussion This study will contribute insights into the impact of communication modality on the balance between creative problem-solving and disclosure in medical settings. By examining the complex links between communication modality, creativity, and disclosure, the findings can have implications for the rapidly growing telehealth field and help inform the design and implementation of effective communication strategies that enhance patient care. Trial registration Trial is registered on ClinicalTrials.gov (Number NCT06784635). We also aim to pre-register this study on the Open Science Framework, as this is a behavioral science study.